Labels used by adolescents to stigmatize people with mental illness - Rosa, Amorim Gabriel Santos (2014)
Background - The stigma against the mentally ill is a major barrier to help-seeking in adolescents for mental health problems. The objective of this study was to investigate the extent of stigma in relation to treatment avoidance in 12-17 year-old school students in Coimbra, Portugal in relation to how they refer to people with mental illness. Methods- This is a qualitative study involving three focus group. The data were gathered in June 2013, as part of the assessment of knowledge on Mental Health Literacy in adolescents. Participants were recruited from three grammar schools (urban, suburban and rural). At the start of the sessions, the students were asked 'What words or phrases might you use to describe someone who experiences mental health problems?' Words and terms used to refer to mental illness were enumerated and grouped in terms of their denotative and connotative meanings. Labels were then derived to capture the key themes attached by the students to the concepts of mental illness. Results - The 23 participating students provided 44 words and terms to describe a person with mental illness. Six themes were identified from the data. The two first themes called 'popular derogatory terms' (14 items) and 'negative emotional states' (12 items) accounted for more than half of the words examined. The remaining four themes occurred less often and were described as 'use of psychiatric diagnoses' (8 items), 'terms related to violence' (5 items) and 'behavioral problems' (5 items). Conclusion - Findings suggest the hypothesis that help-seeking by mentally ill adolescents may be improved by interventions that address both their lack of information about mental illness, and those which reduce their strong negative emotional reactions towards people with mental illness.